The Effect of the Think-Pair-Share (TPS) Learning Model on the Mathematical Problem-Solving Ability of Grade VII Students - Sindi Aulia; Arini Hidayati (Journal of Creative Power and Ambition (JCPA), 2026)
The low achievement of students' mathematical problem-solving abilities is frequently caused by the perception that mathematics is an abstract and difficult subject, particularly regarding seventh-grade algebraic material. Conventional learning processes tend to make students passive in constructing their own understanding. Therefore, an instructional model is required that can stimulate student independence, collaboration, and critical thinking skills through systematic problem-solving stages. This study aims to determine whether or not there is a significant influence of implementing the Think-Pair-Share (TPS) learning model on the mathematical problem-solving ability of seventh-grade students on algebraic material. This study used a quantitative approach with a Quasi-Experimental research type, utilizing the Nonequivalent Control Group Design. The data collection instrument consisted of mathematical problem-solving essay tests designed based on Polya's stages. The final data analysis technique used for hypothesis testing was the non-parametric statistical Mann-Whitney U Test. Based on the results of data analysis, it can be concluded that the implementation of the Think-Pair-Share (TPS) learning model shows a significant influence on the mathematical problem-solving ability of seventh-grade students on algebraic material.